APPRAISAL OF PERSUASIVE POLITICAL COMMUNICATION EFFECTS ON YOUTHS’ PARTICIPATION IN POLITICS IN NIGERIA - Anyanwu, B.J.C.; Onuoha, Ikenna Noel (African Journal of Social and Behavioural Sciences, 2022)
This study investigated the role of persuasive communication in influencing political participation among youths in Nigeria. The roles of persuasive political news media, online citizen media, online political interaction, and offline political discussions in shaping political participation were examined. While there is evidence in the literature that persuasive communication significantly influences political participation among youths, especially when the said communication is done on social media platforms, there seems to be a consensus that different persuasive communication activities exert their special influences in shaping political participation via unique social normative and cognitive processes. However, it can also be deduced from the literature that persuasive communication is not enough to make the youths actively participate in political issues; the positive influence of this communication on political participation is completely mediated by the youths’ experiences (schema), political interpersonal communication with peers and social normative and cognitive processes. Both online political interaction and offline political discussion exert strong direct and indirect influences on political participation.